Student Practicum Competencies through Lesson Study with the application of Argument Driven Inquiry - Nurhasana Siregar; Rodiah Ulfah Lubis; Puspa Riani Nasution (Jurnal Pembelajaran Fisika, 2021)
This study intends to analyze the student's practicum competencies through Lesson Study activities by applying the Argument-Driven Inquiry learning model which was studied using qualitative research with descriptive qualitative analysis techniques. The sample is 13 students in the fourth semester of physics education. Based on students’ practicum reports, the percentage of learning outcomes in the first Lesson Study was 70.91, the second Lesson Study was 84.83. The indicators of student practicum competencies include the competencies of synthesis, cooperation, communication, and independence, each percentage gain is 41.03%; 47.12%; 54.49%; 45.77% in Lesson Study 1, and 77.56%; 82.69%; 78.85%; 76.92% in Lesson Study 2. Student responses to practicum competencies for each indicator are 80.13%; 83.33%; 82.05%; 78.21%. These show that there is a positive change in student practicum competencies and the reflection’s results show that there is an accurate prediction of the final measurement result and knowing how to obtain the right measurement outcome. Keywords: practicum competencies, lesson study, reflectionDOI: http://dx.doi.org/10.23960/jpf.v9.n2.202111